Mental Fatigue Assessment in Different Thermal Environments – Protocol - Costa, Emília Quelhas; Baptista, João Santos; Carvalho, Jorge (Journal of Tourism, Sustainability and Well-being, 2018)
Environmental and personal characteristics influence the behavior of individuals through the limitation of effort levels by a more or less rapid induction of fatigue. In particular, mental fatigue is recognized as a major cause of errors leading to accidents. As a consequence, thermal environment study has gained increasing importance in recent years. In order to contribute to enlarge the knowledge in this field, this work aims to present an essay protocol to evaluate the influence of the thermal environment on mental fatigue, based on electroencephalographic (EEG) analysis. With this purpose an exploratory study was held with 36 volunteers to validate the protocol. Volunteers simulated an administrative task for one hour. Fatigue assessment was carried out by analyzing Alpha and Beta waves amplitude over time. Assays were performed in a climatic chamber with controlled temperature and humidity: 22°C (40 and 80% RH) and 32°C (40 and 80% RH). Results suggest that both temperature and humidity influence the amplitude of the EEG signal (Alpha and Beta waves) in both hemispheres. The greatest amplitudes were found whenever environmental temperature and/or relative humidity values were higher. At the end of the article the advantages and limitations of mental fatigue assessment are discussed.